Encapsulation of room temperature ionic liquids by miniemulsion polymerisation for application in low-emitting latex coating - Kong, Yiyang (2016)
Latex coating has gained increasing attention. It is prepared by mixing latex, a dispersion of polymer particles in water, with pigments, fillers, and additives. As water is used as solvent, emission of VOCs can be minimised. However, coalescing agent emission and excessive surfactant residual hinder its further applications. To solve these two problems, we tried to use room temperature ionic liquid (RTIL), a potential multi-functional additive with non-volatility, to replace coalescing agent, and employed silica nanoparticle as emulsifier to stabilise the latex. The preparation of latex containing 1-octyl-3-methylimidazolium hexafluorophosphate (C8mimPF6), the target RTIL in this study, could be achieved by encapsulating C8mimPF6 inside particles via miniemulsion polymerisation. Two kinds of emulsifiers, surfactant and silica nanoparticle were employed to stabilise miniemulsion/latex. To achieve this encapsulation, three steps were carried out in succession: preparation of miniemulsion, miniemulsion polymerisation, and characterisation of latex containing C8mimPF6. Factors, especially C8mimPF6, on initial droplet size and stability of miniemulsion, yield and stability of polymerisation process, and final functionality of latexes were systemically investigated. For miniemulsion stabilised by surfactant, sodium dodecyl sulfonate (SDSO), initial droplet size decreased apparently with the addition of C8mimPF6 up to 1 wt% due to the effect of C8mimPF6 on oil phase viscosity and interfacial tension. During storage, C8mimPF6 above 10 wt% led to the frequent coalescence of droplet as it decreased the absolute zeta potential. During polymerisation, when initiated by hydrophobic 2, 2-azobis (isobutyronitrile) (AIBN), C8mimPF6 had a promoting effect on the reaction rate at low concentrations, but this effect might reverse upon certain C8mimPF6 concentrations, e.g. 10 wt%; while initiated by hydrophilic hydrogen peroxide/ascorbic acid (H2O2/AAc), this promoting effect faded even at low C8mimPF6 concentrations. The different limiting factors, kinetic or transfer of radicals, might determine the reaction rate with different types of initiator. The final particle size depended on the nucleation mechanism as well as the coalescence of droplets/particles during polymerisation. For the final latex, C8mimPF6 promoted the decrease in glass transition temperature (Tg) and the deformation of particles, due to its function as an external plasticiser with low Tg and compatibility with poly (methyl methacrylate) (PMMA) inside particles; the film became more flexible and had better thermal stability in the present of C8mimPF6. To solve excessive surfactant residual, silica nanoparticles were employed as emulsifiers to stabilise miniemulsion. Adding 1 wt% C8mimPF6 resulted in a sharp decline in droplet size, due to the combined effects of C8mimPF6 on the viscosity of oil phase and interfacial tension. Because of the low absolute zeta potential, creaming or sediment occurred at different C8mimPF6 concentrations, determined by the density difference between the oil and water phases. During polymerisation, a higher yield could be achieved by AIBN, compared with H2O2/AAc. The change of C8mimPF6 concentration had a greater impact on product stability e.g. only above 10 wt% C8mimPF6, stable products could be achieved. For product yield, there was only small effects, varying from 85 wt% to 91 wt% with C8mimPF6 changing from 0 to 30 wt%. For the final latex, the Tg of the obtained polymer decreased with the increase of C8mimPF6 concentration, indicating its function as an external plasticiser, but deformation of particles was limited, probably due to obstacles of silica nanoparticles on the surface of particles. Compared with bulk PMMA, films containing C8mimPF6 had a better thermal stability at temperatures ranging from 300 oC to 450 oC.